REAKSI PASAR TERHADAP STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - admin, Syarifah Khairunnisa B11112032 (Jurnal Manajemen Update, 2016)
The aim of this research is to analyze the reaction of stock split information toward the abnormal return and trading volume in the companies listed in Indonesian Stock Exchange (IDX). The research samples are the companies that have done the stock split in the period between 2008 and 2014. Using purposive sampling, there are 22 companies that fulfill the criteria. Event study method is selected for this research and paired sample t-test is used to test the hypotesis. The result of the paired sample t-test shows that there are differencesÂ  between the abnormal return (in average) of stocks before and after the stock split. The researcher found that the abnormal return (in average) of stocks before stock split is -0,077914 compared to -1,541409 after stock split. It means that the market is not efficient yet. While, there is no significantly difference in stock trading volume in the period of stock split, which has average stock trading volume 0,008190 before stock split and average stock trading volume 0,028235 after stock split.